PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN ASERTIVITAS SISWA TERISOLIR KELAS XI IPS SMAN 2 TAMBANG - Martha agustina; Elni Yakub; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims: 1) To determine the students' level overviewassertivity isolated before being given guidance services. 2) To know the description ofthe implementation process of group guidance to the increasing assertiveness ofstudents isolated in the experimental group. 3) To know the description assertivityincrease student isolated after the giving of guidance services group in the experimentalgroup. 4) To determine differences in the level of assertiveness of students isolatedbefore and after the implementation of guidance services group in the experimentalgroup. 5) To know the description of differences in levels of assertiveness isolatedstudents in the control group. 6) To know the effect of group counseling services to theincreasing assertiveness of students isolated. 7) To know the differences in the level ofassertiveness of students between the experimental group and the control group. Themethod used is an experimental method with pretest-posttest control group design.Subjek were students of class XI IPS SMA 2Tambang numbered 30 people students.Data technique were analyzed using the Wilcoxon test were performed with SPSS 16 isobtained Z = -2.840 and Asymp , Sig. (2-tailed) = 0.005. Asymp value. Sig. (2-tailed)<0.05 (0.005 <0.05) Thus, Ho is rejected and Ha accepted, which means there is asignificant difference to the increasing assertiveness of students before to after the givengroup counseling services. And then coefficient Spearman correlation test through SPSS16 is obtained r2 = 0.437. Furthermore, the magnitude of the effect of group counselingservices to the increasing assertiveness of students isolated amounted to 43.7%.Keyword : group counseling services, assertivity